2019
DOI: 10.33258/birle.v2i4.505
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Speaking Achievement by Using Storytelling Technique

Abstract: This study was aimed to improve the students’ speaking achievement by using storytelling technique. The subject of the study was the eight grade students of Public Junior High School 22 Medan in academic year 2018/2019. This study was conducted by applying Classrom Action Research (CAR), which had been conducted in two cycles and each cycle consisted of three meetings. The instruments of collecting data were quantitative data (speaking test) and qualitative data (observation checklist and field notes). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Its importance comes from the fact that it involves three different activities (role-play, storytelling, and voice recording) integrated into one strategy. The results of the current study come in line with the results of other studies, such as Le (2018), Ayuningtias et al (2019), Neupane (2019), and Sembiring and Ginting (2019).…”
Section: The Impact Of Iis On Fluencysupporting
confidence: 92%
See 1 more Smart Citation
“…Its importance comes from the fact that it involves three different activities (role-play, storytelling, and voice recording) integrated into one strategy. The results of the current study come in line with the results of other studies, such as Le (2018), Ayuningtias et al (2019), Neupane (2019), and Sembiring and Ginting (2019).…”
Section: The Impact Of Iis On Fluencysupporting
confidence: 92%
“…In another study, Sembiring and Ginting (2019) used storytelling techniques to improve the speaking skills of eighth-grade students. The results of the study showed that storytelling enhanced the oral skills of those students since the mean score increased in the post-test by 57.2 %.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Storytelling is defined as the art of telling stories through words and actions to engage an audience (James et al, 2019). In other words, it is not the same as reading a story because it narrates a story from memory (Sembiring & Ginting, 2019); because of the numerous benefits embedded in stories, storytelling is one of the best ways to help EFL students learn the four skills in their first and second languages. It also improves learners' communication abilities (Utami et al, 2018).…”
Section: Nomentioning
confidence: 99%
“…The Reading to Learn (R2L) model has a main focus on teaching students to read texts and then gain a deeper understanding of the contents of the reading by writing what they have learned (Rose & Martin, 2012). The R2L model can be applied with a syntax that can express students' understanding through ideas or ideas they get from reading material (Husein, Sembiring, et al, 2022). There are four stages in implementing the R2L strategy, including (Husein, Siregar, et al, 2022): 1.…”
Section: Introductionmentioning
confidence: 99%